The Algerian War theme in AngloAmerican Literature The Case of Robert Irwin's Novel: The Mysteries of Algiers - Yousfi,Bilal; Kalfa, Sayah (University of Ammar Theledji -Laghouat, 2022)
This dissertation thesis deals with the Algerian War theme in Anglo-American literature, the war had been a subject of literary production in the Anglo-American range during a period between the sixties and the eighties. This study investigates the scope that the Algerian War took in the Anglo-American literary production, the motives of the writers and the characteristics of those literary works. The aim is to shed light on this particular area that have a significance to the Algerian academia since it deals with the most important period in the Algerian contemporary history. This study uses a comparative approach between fiction and historical records, to find out how the Algerian War is represented from an Anglo-American point of view. the study case in this study is The Mysteries of Algiers, a novel by the British writer Robert Irwin. The research outcomes suggest that the Algerian War was a topic of interest to some Anglo-American writers. In addition, They were, in general, sympathetic with the Algerian cause, as a reaction to the atrocities of war. Beside that they had knowledge about the specificities of the Algerian War, however, their view is guided by a western (orientalist) view when it comes to deal with the Algerian people and culture. This research opens the gate to further discussions concerning other aspects of the Algerian War literary representations in English, not forgetting the Algerian presence in the Anglo-American Literature concerning other periods